Aesthetics on the web: effects on approach and avoidance behaviour. Issue 1 (2nd January 2016) - Strebe, Rita
Abstract : This paper describes an experimental investigation that tested the impact of the aesthetic impression on approach and avoidance behaviour by measuring relevant behavioural variables while interacting with websites. These variables included dwell time, number of retrieved web pages and reading time proportion. This approach extends previous research that primarily used surveys as the data collection method. Two levels of experiencing aesthetics were integrated into the research set-up: the first measures the reflective aesthetic appreciation and the second captures the immediate affective visual impression, the latter being operationalised through an affective priming experiment. Seventy participants took part in the main experiment and explored 10 real stimulus websites. Results showed that participants stayed significantly longer, retrieved more web pages and spent more time reading on websites that they preferred in their aesthetic impression. Aesthetics on the web are thus revealed to be of behavioural relevance. Effect sizes indicate only small to medium effects though. No statement is possible concerning the respective share of the two levels of aesthetic processing in this effect, because the study did not successfully delineate the effectiveness of affective and reflective aesthetic experiences in the course of exploration.